HUBUNGAN AKREDITASI PUSKESMAS DENGAN TINGKAT KEPUASAN PASIEN DI PUSKESMAS - Rahmilah, Mitha; Nur, Hirza Ainin; Putra, Ryryn Suryaman Prana; L.Tobing, Hendri Parluhutan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract:Puskesmas is the frontline in organizing basic health efforts by prioritizing promotive and preventive efforts to achieve public health status. Puskesmas accreditation is one of the regulatory mechanisms that aims to encourage efforts to improve the quality and performance of Puskesmas services. The purpose of the study was to determine the relationship between puskesmas accreditation and the level of patient satisfaction at the puskesmas. The research design used in this study was cross sectional. The study was conducted at 2 health centers in Semarang Regency. The research was conducted in July 2024. The sample amounted to 240 respondents. The sampling technique used in this study was purposive sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between the level of accreditation of health centers (p value: 0.042) on patient satisfaction. It is recommended that the health center improve and improve the quality of health services from all dimensions of reliability, assurance, tangiable, empathy and responsiveness and conduct regular and continuous patient satisfaction surveys to evaluate the health service performance of the Puskesmas.Keywords: Accreditation, Satisfaction, Health Center.